Evaluation of the MAScIR SARS-CoV-2 M Kit 2.0 on the SARS-CoV-2 Infection. (7th February 2023) - Zouaki, Amal; Kabbaj, Hakima; El Amin, Ghizlane; Ouadghiri, Mouna; Belefquih, Bouchra; Ibrahimi, Azeddine; Seffar, Myriam
Abstract : SARS-CoV-2 is a major public health problem worldwide. Since its emergence, several diagnostic kits have been developed to ensure rapid patient management. The aim of our study is to check the performance of the new Moroccan SARS-CoV-2 detection kit: MAScIR SARS-CoV-2 M 2.0. The following parameters were studied: repeatability, reproducibility, analytical specificity, analytical sensitivity, and comparison with the GeneFinder™ COVID-19 Plus RealAmp Kit. In addition, an external quality evaluation comprising five specimens was carried out as part of an international program for the external quality evaluation of sublaboratories of the WHO and the Laboratory Office of the National Institute of Hygiene of Morocco. The results of all parameters studied showed an analytical performance that complied with the requirements of the method verification/validation protocol adopted by the Central Laboratory of Virology and met the recommendations of COFRAC (French Accreditation Committee). During the current study, the sequencing of some randomly selected positive samples was performed, among which the carriers of the Alpha variant, the Delta variant, and the Omicron variant were detected. These results allowed us to deduce that this kit was valid for detecting these three variants.